Design of cost-effective real time tremor alerting system for patients of neurodegenerative diseases. (2022) - Premkumar, M.; Ashokkumar, S.R.; Jeevanantham, V.; Anu Pallavi, S.; Mohanbabu, G.; Sathesh Raaj, R.
Abstract: In recent years, many people are affected by neurodegenerative disorders like Alzheimer, Parkinson, motor neuron disease, and Chorea. Brain function loss, movement problems and typically cognitive impairments occur from their influence on the central nervous system. In this situation, early symptom monitoring and assessment are essential for enhancing the tremor patient life. Here, we propose embedded system development, for early alerting of tremors by integrating heart rate and MEMS sensors. In the created system, a collection of different four sensors are linked to a development board. This device can track the geographical location of Alzheimer's patients and detect tremor/movement, as well as accidental falls. Using GSM connectivity, a remote administrator may collect data from the development board. A data compression method is constructed directly on board to improve data transmission efficiency and reduce power usage.